Magic Box Media And Project-Based Pedagogy Build Inclusive Early Childhood Competencies: Media Magic Box Dan Pedagogi Berbasis Proyek Membangun Kompetensi Anak Inklusif - Eka Nurjanah; Iis Prasetyo (Academia Open, 2026)
General Background Early childhood education provides a critical foundation for optimizing cognitive, motor, language, and interpersonal domains through responsive, child-centered environments. Specific Background Students with special needs within integrated classrooms frequently face integration challenges, displaying anxious behaviors, egocentrism, and difficulties in regulating their feelings. Knowledge Gap Current instructional materials and play frameworks are rarely designed to facilitate meaningful interpersonal interactions or address the specific collaborative deficits present in diverse classrooms. Aims This study investigates the application of collaborative tasks supported by an interactive educational toy to support young learners. Results Through two action research cycles, participant scores rose significantly from an initial 56.25% to 80.73%. The most substantial behavioral growth occurred in the capacity to articulate feelings appropriately, which increased by 41.67%, alongside moderate overall developmental gains indicated by an N-Gain of 0.56. Furthermore, educators shifted from rigid lesson planning to flexible, empathetic facilitation and dynamic classroom management. Novelty This intervention uniquely integrates collaborative problem-solving structures with tactile educational tools to simultaneously transform student interpersonal behaviors and professional teaching paradigms. Implications Deploying structured, authentic play activities offers a proven framework for cultivating supportive relationships and advancing holistic development in diverse educational settings. Highlights The intervention generated a moderate N-Gain score of 0.56, indicating steady behavioral progress. Students with special needs demonstrated a 41.67% increase in their capacity to express feelings appropriately. Educators transitioned toward flexible planning and exhibited higher empathy during classroom management tasks. Keywords Collaborative Tasks; Educational Toys; Interpersonal Skills; Teacher Paradigms; Action Research